2021
DOI: 10.5530/pj.2021.13.8
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Screening and Antioxidant Activities of the Seedling Extracts from Inca Peanut Plukenetia volubilis

Abstract: Background: Plukenetia volubilis L., Inca peanut is an oleaginous plant, widely cultivated as commercially in South East Asia, especially in Thailand. The oil from the seed plant is a greatest interesting a natural source. Objectives: The aims of this study were investigated phytochemical screening, to evaluated the total flavonoids and phenolic compound contents as well as antioxidant activities of seedling extract from P. volubilis. Methods: The dried P. volubilis seedlings of 21 days growing period were ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 31 publications
(33 reference statements)
0
10
2
Order By: Relevance
“…In some plants, hydro-alcoholic and alcoholic extracts were determined total phenolic content using Folin-Ciocalteu’s reagent with gallic acid and total flavonoid content using aluminium chloride with quercetin. It was found that flavonoid content was higher than total phenolic content ( Agbo et al, 2015 , CI and Indira, 2016 , Puangpronpitag et al, 2021 ). The other active compounds of phenolic and flavonoid compounds may be used and obtained the appropriated the amount of active compounds in their extracts ( Vongsak et al, 2013 ).…”
Section: Discussionmentioning
confidence: 98%
“…In some plants, hydro-alcoholic and alcoholic extracts were determined total phenolic content using Folin-Ciocalteu’s reagent with gallic acid and total flavonoid content using aluminium chloride with quercetin. It was found that flavonoid content was higher than total phenolic content ( Agbo et al, 2015 , CI and Indira, 2016 , Puangpronpitag et al, 2021 ). The other active compounds of phenolic and flavonoid compounds may be used and obtained the appropriated the amount of active compounds in their extracts ( Vongsak et al, 2013 ).…”
Section: Discussionmentioning
confidence: 98%
“…The results of antioxidant activity analysis on sample m 1 t 1 (5% maltodextrin, temperature 50⁰C) showed a result of 0.075%, which is the antioxidant activity of this powdered Sacha inchi extract including a weak level category. According to Puangpronpitag et al (2021), the IC 50 result on Sacha inchi seed oil is 0.007 ± 0.001 (mg/mL). Still, in this study at 50⁰C, the antioxidant activity is already weak, another factor that causes antioxidant levels in this powdered Sacha inchi extract may be due to the length of drying carried out.…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…Extracts of various medicinal plants are used in different industries such as pharmaceuticals, food industries and for nanomedicine (Hayat et al, 2023;Hussain et al, 2023;Iram et al, 2023;Riasat et al, 2023;Saleem et al, 2023;Sana et al, 2022;Syed et al, 2023;Zahra et al, 2023;Zawar et al, 2023;Rauf et al, 2023; Effect of maltodextrin concentration and drying temperature on the physicochemical characteristics of Sacha inchi Naveed et al, 2022a;Naveed et al, 202b). Sacha inchi (Plukenetia volubilis L.) is a shrub that grows vines and is commonly known as Sacha beans, mountain beans, or Inka beans (Puangpronpitag et al, 2021). Sacha inchi is an annual plant with slightly hairy textured leaves and belongs to the Euphorbiaceae family.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effectiveness of these mechanisms is due to the presence of chemical components such as In Peru, sacha inchi seed oil is conventionally applied as a regular skin care oil to promote skin health [5]. According to the research of Puangpronpitag et al [6], sacha inchi seed oil has significant antioxidant activity, with an IC50 value of 0.007 ± 0.001 (mg/mL). Hadzich et al [7] and Chirinos et al [8] also reported that the bioactive compounds contained in sacha inchi seed oil have the potential to act as antioxidants, including vitamin E, vitamin A, tannins, phytosterols, phenolic compounds, and terpenoids.…”
Section: Introductionmentioning
confidence: 99%